Modified work-rest schedule of the handloom weavers: An ergonomic study - Santu Durlov; Somnath Gangopadhyay; Subhashis Sahu (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: A sustainable work schedule is created by employing proper work and recuperation cycles, as well as balancing high- and low-effort tasks. The work of the handloom weaver was physically and mentally taxing. However, they do not take breaks and work nonstop. Short breaks are good for both physical work and job-related mental and cognitive stress. Therefore, a quick break is used as an intervention. METHODS: Participants in this study included 100 handloom weavers. A modified work-rest plan consists of 50 min of labor and 10 min of rest per hour. To order to calculate Brouha's index, recovery heart rate data were collected after work for 3 min while the participant was seated. Using the flicker-fusion frequency test, visual tiredness was assessed. RESULTS: A newly developed work-rest cycle lessens tiredness and becomes more effective over time. The newly created work-rest plan for the handloom weavers dramatically reduces perceived exertion and energy expenditure. CONCLUSION: The modified work-rest schedule decreased cardiovascular and mental stress. This work-rest schedule will therefore reduce fatigue and help with the work if it is used in this sector.